Enzyme-responsive peptide dendrimer-gemcitabine conjugate as a controlled-release drug delivery vehicle with enhanced antitumor efficacy. (June 2017) - Zhang, Chengyuan; Pan, Dayi; Li, Jin; Hu, Jiani; Bains, Ashika; Guys, Nicholas; Zhu, Hongyan; Li, Xiaohui; Luo, Kui; Gong, Qiyong; Gu, Zhongwei
Graphical abstract: Abstract: Stimuli-responsive peptide dendrimer-drug conjugates have presented significant potential for cancer therapy. To develop an effective nanoscale chemotherapeutic prodrug, we developed a novel enzyme-responsive PEGylated lysine peptide dendrimer-gemcitabine conjugate (Dendrimer-GEM) based nanoparticle via the highly efficient click reaction. Owing to the glycyl phenylalanyl leucyl glycine tetra-peptide (GFLG) as an enzyme-cleavable linker to conjugate gemcitabine (GEM), the prepared nanoparticles were able to release drug significantly faster in the tumor cellular environments, which specifically contains secreted Cathepsin B, quantifiably more than 80% GEM was released with Cathepsin B compared to the condition without Cathepsin B at 24 h. This nanoparticle demonstrated enhanced antitumor efficacy in a 4T1 murine breast cancer model without obvious systemic toxicity, resulting in significantly suppressed relative tumor volumes (86.17 ± 38.27%) and a 2-fold higher value of tumor growth inhibition (∼90%) than GEM·HCl treatment. These results suggest that the PEGylated peptide dendrimer-gemcitabine conjugate can be an effective antitumor agent for breast cancer therapy. Statement of Significance We found that the functionalized dendrimer based nanoscale drug delivery vehicles exhibited enhanced therapeutic indexes and reduced toxicity as compared to the free drug gemcitabine. Compared with current nanoparticles, such as dendritic anticancer drug delivery systems, the new design was capable of self-assembling into nanoscale particles with sizes of about 80–110 nm, which is suitable as antitumor drug delivery vehicle due to the potential longer intravascular half-life and higher accumulation in tumor tissue via EPR effect. Owing to the optimized architecture, the system was given the enzyme-responsive drug release feature, and showed excellent antitumor activity on the 4T1 breast tumor model due to the evidences from tumor growth curves, immunohistochemical analysis and confocal laser scanning microscopy. Meanwhile, no significant side effect was observed by histological analysis. This study demonstrated that PEGylated peptide dendritic architecture may be used as efficient and safe nanoscale drug delivery vehicle for cancer therapy.